A3_6 The blind spot of the Human eye - Ryan, Liam; Karazhov, Dennis; Booth, Tim (Physics Special Topics, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> In this paper we demonstrate that the blind spot of the human eye can block out small objects from our visual field. We use baseball as an example and it was found that at a certain angle the ball could not be seen for some distance. We then showed that the batter does not have enough time to react and hit the ball when it reappears in the visual field.